EFFECT OF PROTON IRRADIATION ON THE STRUCTURE DEVELOPMENT OF POLYETHYLENE TEREPHTHALATE FIBERS: EFFECT OF PROTON IRRADIATION ON THE STRUCTURE DEVELOPMENT OF POLYETHYLENE TEREPHTHALATE FIBERS - Velev, Valentin; Popov, Anton; Arhangelova, Nina; Kyurkchiev, Pencho; Hristov, Hristo; Bello, Michele; Moschini, Giuliano; Uzunov, Nikolay (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The influence of proton irradiation on the structural changes in partially crystalline poly(ethylene terephthalate) (PET) filaments has been investigated using a wide-angle X-ray scattering (WAXS). Experimental data about the role of the exposure dose and the irradiation conditions in the processes of destruction and crosslinking in the irradiated objects have been obtained. The structural changes and the packing density of the macromolecular chain segments of the polyethylene terephthalate filaments irradiated with different doses have been analyzed. A mechanism of the structural reorganization initiated by the irradiation has been supposed on the basis of the changes in the geometry of the intensive distribution of the X-ray diffraction patterns of the objects.